The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1182/blood-2003-04-1304
|View full text |Cite
|
Sign up to set email alerts
|

Annexin II mediates plasminogen-dependent matrix invasion by human monocytes: enhanced expression by macrophages

Abstract: Monocytes and macrophages participate in a wide variety of host defense mechanisms. Annexin II, a fibrinolytic receptor, binds plasminogen and tissue plasminogen activator (t-PA) independently at the cell surface, thereby enhancing the catalytic efficiency of plasmin production. We demonstrated previously that annexin II on the surface of both cultured monocytoid cells and monocyte-derived macrophages promotes their ability to remodel extracellular matrix. Here, we demonstrate that human peripheral blood monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
95
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 73 publications
9
95
1
2
Order By: Relevance
“…By functioning as a receptor for ␤ 2 GPI, annexin II is a target not only for anti-annexin II antibodies but also for anti-␤ 2 GPI antibodies, which are direct inducers of TF overexpression and thus are significantly associated with thrombosis in the setting of APS (18). Recently, it has also been demonstrated that annexin II plays an important role in human monocyte/macrophage-directed migration and recruitment and that it is activated on progression from monocytes to macrophages (24). Thus, annexin II might constitute a common receptor for aPL induction of monocyte activation.…”
Section: Discussionmentioning
confidence: 99%
“…By functioning as a receptor for ␤ 2 GPI, annexin II is a target not only for anti-annexin II antibodies but also for anti-␤ 2 GPI antibodies, which are direct inducers of TF overexpression and thus are significantly associated with thrombosis in the setting of APS (18). Recently, it has also been demonstrated that annexin II plays an important role in human monocyte/macrophage-directed migration and recruitment and that it is activated on progression from monocytes to macrophages (24). Thus, annexin II might constitute a common receptor for aPL induction of monocyte activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the annexin A2 heterotetramer has been identified as a receptor for plasmin-induced signaling in human monocytes (25). Moreover, annexin A2 has been linked to plasminogen-dependent matrix invasion by monocytes (46,47). Annexin A2, a member of a family of proteins that bind anionic phospholipids in a Ca 2ϩ -dependent manner, exists in three forms, a monomer (p36), a heterodimer, or a heterotetramer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have implicated ANXA2 in various biological functions, including mitogenic signal transduction, fibrinolysis, immune response, proliferation, carcinogenesis and tumor progression (7)(8)(9)(10)(11). ANXA2 has been demonstrated to be a co-receptor for both plasminogen and tissue-type plasminogen activator, which cleaves inactive plasminogen to yield the active serine proteinase, plasmin (12,13). Subsequent studies elucidated that the conversion of plasminogen to plasmin is induced by ANXA2 promoting metastasis, which leads to the activation of metalloproteinases, degradation of extracellular matrix components, and promotion of neoangiogenesis (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%